2017
DOI: 10.1038/srep43862
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of linguistic laws in human voice

Abstract: Linguistic laws constitute one of the quantitative cornerstones of modern cognitive sciences and have been routinely investigated in written corpora, or in the equivalent transcription of oral corpora. This means that inferences of statistical patterns of language in acoustics are biased by the arbitrary, language-dependent segmentation of the signal, and virtually precludes the possibility of making comparative studies between human voice and other animal communication systems. Here we bridge this gap by prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 83 publications
(129 reference statements)
5
22
0
1
Order By: Relevance
“…Interface 14: 20170231 across all recordings, then the number of peaks identified would be influenced by arbitrary recording conditions among other factors. Nevertheless, analyses reported in the electronic supplementary material show that the results are robust to moderate changes in threshold settings [18,19].…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Interface 14: 20170231 across all recordings, then the number of peaks identified would be influenced by arbitrary recording conditions among other factors. Nevertheless, analyses reported in the electronic supplementary material show that the results are robust to moderate changes in threshold settings [18,19].…”
Section: Methodsmentioning
confidence: 93%
“…AF analysis and similar methods have been used in prior studies of speech event series [15,[17][18][19]. Together, these studies showed that hierarchical temporal structure is present in speech at multiple timescales.…”
Section: Introductionmentioning
confidence: 84%
“…the (average) duration in time of the word, because that may yield a better estimate of the actual energetic cost of a word and also because our research on language laws is to some extend limited by the information that is transcribed and the writing conventions, that add some degree of arbitrariness. These limitations have been overcome to a large extent in novel investigations of language laws in pure voice [14].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…These laws are regarded as universal although the only evidence of their universality is that they hold in every language where they have been tested so far [11]. Because of their generality, these laws have triggered modeling efforts that attempt to explain their origin and support their presumable universality with the help of abstract mechanisms or communication principles [12,13], or exploring directly from voice those statistical patterns in levels under the phoneme scale [14]. Therefore, investigating the experimental conditions under which these laws surface is crucial.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several methods to map time series into graphs have been proposed, under the hypothesis that appropriate graph representations can preserve the original time series information while providing alternatives to deal with nonlinearity and multiscale issues typical of complex signals [1][2][3]. This line of research represents a bridge between nonlinear signal analysis and complex network theory, and has been successfully applied to extract meaningful information from a variety of different systems in physics [4,5], finance [6][7][8], engineering [9], and neuroscience [10,11].…”
Section: Introductionmentioning
confidence: 99%